Keperawatan pada Ny. D dengan Gangguan Sistem Endokrin: Post-Op Tumor Mammae Dextra di Ruang Mawar 2 RSUD Dr. Soeselo Kabupaten Tegal - Desy Liani; Ahmad Zakiudin; Yusriani Saleh Baso (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Post-operative care is a critical phase in the recovery process, beginning immediately after the completion of surgery until the patient is stabilized and transferred to the inpatient ward. Among various surgical procedures, lumpectomy is a common intervention performed to manage mammary tumors, aiming to preserve breast tissue while removing the tumor (Arif et al., 2021). This paper presents a case study of Mrs. D, a patient with an endocrine disorder who underwent a right breast lumpectomy at Mawar 2 Ward, Dr. Soeselo Regional General Hospital, Tegal Regency. The study employed a descriptive method to explore the patient’s condition and nursing interventions. Upon assessment, the main complaint reported by the patient was pain localized in the post-operative area. Based on the findings, two primary nursing diagnoses were established: acute pain related to surgical trauma and knowledge deficit related to post-operative care and self-management. Nursing interventions were designed and implemented according to the Indonesian Nursing Diagnosis Standard (SDKI), the Indonesian Nursing Outcomes Standard (SLKI), and the Indonesian Nursing Interventions Standard (SIKI). Interventions included pain management strategies, such as pharmacological support and non-pharmacological relaxation techniques, as well as health education to improve patient knowledge and self-care ability. The case highlights the importance of comprehensive nursing care that addresses both physical discomfort and the patient’s understanding of recovery, thereby promoting optimal health outcomes after breast surgery.